Formulation and In Vitro Evaluation of Levetiracetam Transdermal Patches - Bariki Rajasekhar; Avula Bhojaraju; G Vinod Kumar Reddy; Gudipogula Susmitha; Harijana James; Kammara Jyothi (Asian Journal of Pharmaceutical Research and Development, 2026)
Long-term epilepsy management requires maintaining stable therapeutic plasma concentrations, which is often challenging with orally administered Levetiracetam because of its short dosing interval requirements and extensive hepatic first-pass metabolism. The present investigation aimed to formulate and evaluate a novel matrix-type transdermal drug delivery system (TDDS) employing a synergistic combination of natural Ficus carica fruit mucilage and synthetic polymers, namely HPMC K100 and Eudragit S100, to achieve sustained and controlled drug release. Five formulations (LTP1–LTP5) were prepared using the solvent casting method. The developed transdermal patches were evaluated for various physicochemical parameters, including weight variation, thickness, folding endurance, and drug content uniformity. Compatibility and possible molecular interactions between the drug and polymers were analyzed using FT-IR spectroscopy, while in vitro drug diffusion studies were performed using a Franz diffusion cell over a 24-hour period.FT-IR analysis confirmed the absence of significant drug–polymer interactions, indicating the chemical stability of Levetiracetam within the polymeric matrix. The prepared patches demonstrated satisfactory uniformity, with drug content ranging from 97.5% to 99.4% and thickness values between 138 and 148 μm. Mechanical characterization revealed good flexibility and durability, with folding endurance values reaching up to 172 folds. Among all formulations, LTP4 containing an optimized ratio of natural and synthetic polymers showed the best performance, exhibiting a cumulative drug release of 98.85% over 24 hours, following matrix diffusion-controlled release kinetics.The study concludes that the optimized LTP4 transdermal patch successfully provided sustained release of Levetiracetam and may serve as a promising non-invasive alternative to conventional oral therapy, potentially improving therapeutic efficacy, patient compliance, and long-term epilepsy management.